Nursing assistance for patients with schizophrenia - Reis, Diêgo Wilton Ricardo dos (2021)
Introduction: Schizophrenia is currently considered one of the main health problems, characterized by changes in thinking, memory, perception and emotion, causing severe mental disorder. Objectives: To describe the role of the nursing team in assisting patients with schizophrenia. Method: This is an integrative literature review, whose selection took place between August 2020 and April 2021. RESULTS: In the management of psychic patients, the role of nursing within the multidisciplinary team, should reflect on the practice and expansion from his professional vision, abandoning the routine activities of the asylum and clinical model, seeking greater interaction and approximation with the subjects. Care practices include assisting the demands presented by the family, caring for people with mental disorders and assessing family burden. In addition to providing information about the disease, as well as encouraging perseverance and adherence to treatment, support through listening, assistance in times of crisis, encouragement to the family during the rehabilitation process, and dealing with the side effects of treatment in terms of biological. Conclusions: Due to the facts presented, it is evident that nursing professionals need actions such as training and continuing education, renewing knowledge, discussing professional-user relationships, developing teamwork and creating spaces for care. Nursing in the face of patients with schizophrenia must consider some skills, such as: effective communication, respect, empathy, and the ability to not judge others.